Reaktualisasi Ajaran Islam: Studi atas Pemikiran Hukum Munawir Sjadzali - Yunahar Ilyas (Al-Jami'ah: Journal of Islamic Studies, 2006)
Referring to Ibn Qayyim al-Jawziyya and Abū Yūsuf, Munawir Sjadzali says that it is necessary to make use of rational thought based on social context in reasoning and applying a legal rule. It is historical that Caliph ‘Umar has practiced this principle in connection with the case of land loot. Instead of taking the land of Syrians as loot, the Caliph ‘Umar took tax from the land owners and distributed the money for military. In another chance, Caliph ‘Umar stopped giving zakāh to mu’allaf group because there is no longer need to give them zakāh in the current situation, different from what Prophet Muhammad and Caliph Abū Bakr have practiced. According to Sjadzali, there are a lot of Islamic legal issues to which an intensive attention and contextualization should be drawn, such as the law of inheritance, zakāh for mu’allaf, bank interest, woman leadership, woman testimony, inter-religious marriage, non Muslim status, slavery, et cetera. The main idea of Sjadzali’s thought is the necessity to take social and cultural context of the society into account at comprehending, and then concluding a legal decision from, Quranic verses concerning with social life, though this will led to not apply the extrinsic meaning of those verses.